An industrial investigation to determine when investment in labour will be effective. (8th September 2008) - Wilson, David; Coleman, Shirley; Herron, Colin
This paper presents the findings of an industrial case study taken from a larger piece of work. The wider research explains the new method of describing culture, which avoids the imprecise thinking, which often plagues the subject. The case study, using companies in the north east of England, shows how influence techniques affect the amount of human intervention permitted in production. A more educated workforce should be allowed greater freedom to change and improve processes, but this freedom is not necessarily controlled by management alone. The mechanism presented accounts for misunderstandings between individuals as well as unhelpful intervention in the process improvement. The results presented here show that influence techniques are a suitable way to incorporate workplace culture into models of the wider world. The investigation suggests that understanding the influence structure in a company provides a sound basis for improving management investment strategies to increase innovation and growth.